Deteksi Keterlambatan Bicara pada Anak Usia 48-72 Bulan Melalui Berbagai Faktor - Lia Kurniasari; Sri Sunarti (Dian Nuswantoro Semarang, 2018)
Speech delay to children in recent years has always increased, the prevalence of speech disorders varies in numbers from 1 to 32% in the normal population. In social life will also be very influential, the child will always feel alone without being able to voice what is desired, and always not understood by others if he wants something with wrong language. This study aims to get the influence was maternal education, maternal employment status and family factor of speech delayÂ to children aged 48-72 months. Quantitative research with cross sectional design in samples of pre school children, the results with P value 0.582 for parent education variables, P value 0,245 for the variable work status of the mother, and P value 0.853forÂ the family history variable. All variables in this study that there was no influence between these variables with the delay in talking to children aged 48-72 months. actually, the development of speaking, speaking of children has begun to be stimulated since the baby, but the form of communication is different from each stage, and if the child is test earlier about their language it will prevent the child from late language development disorders, especially in normal children without history certain diseases from the womb and at birth.